Combined Aerobic and Resistance Exercise Training Improve Hypertension Associated With Menopause - Shimojo, Guilherme Lemos; Silva Dias, Danielle da; Malfitano, Christiane; Sanches, Iris Callado; Llesuy, Susana; Ulloa, Luis; Irigoyen, Maria-Cláudia; De Angelis, Kátia (Frontiers in Physiology, 2018)
The prevalence of hypertension sharply increases in menopausal women. Recent studies have demonstrated that aerobic or resistance training may help control hypertension. In this study, we report that combining aerobic and resistance training may provide an effective therapeutic approach for hypertension control, attenuating inflammation and oxidative stress in ovariectomized rats. Female Wistar and SHR rats were distributed into 4 groups: sedentary control (C), sedentary hypertensive (HR), sedentary hypertensive ovariectomized (HR-O), and combined trained hypertensive ovariectomized (T-HR-O). Combined exercise training was performed on a motor treadmill (aerobic training) and on a ladder adapted to rats (resistance training), in alternate days for 8 weeks. Direct arterial pressure was recorded and oxidative stress and inflammation were evaluated in cardiac and renal tissue. Ovariectomy increases increased mean arterial blood pressure, sympathetic modulation and oxidative stress in spontaneous hypertensive rats (SHR). Combining aerobic and resistance training reduced mean arterial blood pressure (12% vs. HR-O), heart rate (8% vs. HR-O), vascular sympathetic modulation (40% vs. HR-O) and improved baroreflex sensitivity. Combined training reduced cardiac inflammation (TNF and IL-6) and cardiac and renal lipoperoxidation (59% and 57%, respectively vs. HR-O). It also enhanced cardiac (71%) and renal (76%) total antioxidant capacity when compared to HR-O group. In conclusion, combining aerobic and resistance training improves mean arterial blood pressure, cardiovascular autonomic control, preventing cardiac and renal oxidative stress and inflammation in an experimental hypertension model with surgical menopause induced with ovariectomy.